2012
DOI: 10.1134/s107042721201003x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a magnesium aluminum spinel by the burning method

Abstract: Synthesis of MgAl 2 O 4 from a stoichiometric mixture of aluminum and magnesium nitrates by its burning with urea, glycine, sugar, and mixtures of these as a fuel was studied.A transparent ceramic based on MgAl 2 O 4 is a good alternative to the expensive and diffi cultly reproducible single-crystal MgAl 2 O 4 spinel. Optical applications of the transparent ceramic includes IR windows and inert laser shutters [1]. It is known that good properties of a ceramic result from the adequate choice of synthesis method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…A thermally induced redox reaction occurs between an oxidant and fuel. Nitrate salts typically act as oxidants and cation sources, and organic compositions as fuels (Gromov, Tikhomirova, Lokshin, & Kalinnikov, 2012;Ianos & Lazau, 2009;Prabhakaran, Patil, Dayal, Gokhale, & Sharma, 2009). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A thermally induced redox reaction occurs between an oxidant and fuel. Nitrate salts typically act as oxidants and cation sources, and organic compositions as fuels (Gromov, Tikhomirova, Lokshin, & Kalinnikov, 2012;Ianos & Lazau, 2009;Prabhakaran, Patil, Dayal, Gokhale, & Sharma, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Urea, sugar, and their mixtures are suitable fuels for preparing MAS from a stoichiometric mixture of aluminum and magnesium nitrates. Phase-pure MAS powder of crystallite size of 18.4 nm has been formed using sugar-urea as a fuel (Gromov et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The calcination of autoignition product increases the crystallinity of spinel. The combustion technique is an inexpensive method that allows the preparation of highly purified, nano-sized crystalline powders at lower calcination temperatures in significantly shorter time [21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Urea-formaldehyde [21], urea and triethylenetetramine mixture [22], sugar-urea [23], glycine [24], starch [25], alanine [14], citrate [26][27][28], and polyacrylamide [29] were used as fuels in the combustion synthesis of nano-scale MgAl 2 O 4 powders. Generally, in the combustion process, a thermally induced redox reaction takes place between cations and fuel.…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that urea, glycine, sugar, and mixtures of these materials are suitable fuels for synthesis of MAS from a stoichiometric mixture of aluminum and magnesium nitrates by the autoignition method. The single-phase MAS powder with crystallite size of 18.4 nm was obtained when sugar-urea was used as a fuel [24]. Nano-scale powders were successfully synthesized via combustion process using various mixtures of urea, glycine and starch.…”
mentioning
confidence: 99%